De Sitter microstates from T T¯ + Λ2 and the Hawking-Page transition - Coleman, Evan; Mazenc, Edward A.; Shyam, Vasudev; Silverstein, Eva; Soni, Ronak M.; Torroba, Gonzalo; Yang, Sungyeon (Springer, 2022)
Fil: Coleman, Evan. University of Stanford; Estados Unidos